Analysis of offensive tactical organization in volleyball against zonal blocking - Baker, Daniel; Dupont, Jean (Cambridge Sport Science, 2025)
This paper explores the characteristics of zonal blocking and its application in volleyball matches, aiming to identify the most effective offensive tactics when facing zonal blocking. The study provides references for further improving the volleyball training system and the development of volleyball. Conclusion: With the evolution of volleyball and its rules, a variety of offensive methods and tactical combinations have emerged, along with more detailed classifications of blocking forms, each with corresponding offensive strategies. Suggestions: In regular volleyball teaching, specialized analysis and training on offensive tactics against zonal blocking should be conducted. Additionally, multiple offensive tactical systems should be developed to cultivate players' ability to switch and apply offensive tactics flexibly and quickly.